Neuralgic Amyotrophy-Report of 4 Cases - Oosako, Y.; Kamihira, M. (Orthopedics & Traumatology, 1973)
Four cases of neuralgic amyotrophy were seen in our clinic during past years. Their outline is as follows; The youngest patient was a man of 20 years and the oldest was a woman of 69 years. Three of 4 were male. In two cases, Herpes-zoster developed simultaneous with or following to the appearance of muscle weakness. Weakened muscles was localised in the shoulder girdle in two cases but distributed to the forearm too in other two cases. Sensory disturbance was observed in two cases alone, in which cases Herpes-zoster developed. In 3 cases, prognosis was good or fair in 2-3 months but the other case showed no improvement in 3.5 months.